2019
DOI: 10.1515/ijnes-2018-0060
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Indicators of National Council Licensure Examination for Registered Nurses (NCLEX-RN) Success in Nursing Graduates in Newfoundland & Labrador

Abstract: In Canada in 2015, the pass rates on the National Council Licensure Examination (NCLEX-RN) were considerably lower than pass rates on the Canadian Registered Nurse Examination (CRNE) causing nurse educators to express concern regarding the NCLEX-RN. The purpose of this study was to examine the relationship between candidate variables (e. g. academic performance, demographics) on their NCLEX-RN outcome (pass/fail). A cross-sectional data linkage design was employed using multiple sources of data on nursing grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A study found that social supports, ie, peer-group study, mentorship program, and peer-group tutoring, have been considered significant factors to succeed on the exam. 31 Moreover, the facilities and supports mentioned by the participants have been included in the curricula of Economic Partnership Agreements (EPA) between Indonesia and Japan. 32 The agreement stated that the Japanese government is responsible for providing the candidate travel allowance, accommodation and stipend related to the exam and the training tuition fees in collaboration with the employer (the hospital where the candidate works).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that social supports, ie, peer-group study, mentorship program, and peer-group tutoring, have been considered significant factors to succeed on the exam. 31 Moreover, the facilities and supports mentioned by the participants have been included in the curricula of Economic Partnership Agreements (EPA) between Indonesia and Japan. 32 The agreement stated that the Japanese government is responsible for providing the candidate travel allowance, accommodation and stipend related to the exam and the training tuition fees in collaboration with the employer (the hospital where the candidate works).…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] According to Pike et al ., students are now encouraged to incorporate the use of NCLEX-RN preparation resources to enhance their learning and increase their chances of passing. [ 17 ] Likewise, the mentorship of nurse educators in the familiarization of how the questions are structured and how to respond was seen as a significant factor in the success of nurse graduates. [ 29 ] This underscores that nursing schools need to conduct review classes and simulation exams prior to the SNLE to prepare the students by acquainting them with the examination process and to bolster their confidence prior to taking the examination.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Prelicensure exams, GPA, and test preparation strategies predicted higher success on the CPNRE. [ 16 17 18 ] While much has been written on the predictors of licensure examination success from countries with a strong foundation of nursing, no known similar studies have been conducted in Saudi Arabia. It is essential to look at the factors that influence the performance of nurse graduates on nurse licensure exams in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%